2019
DOI: 10.1080/23802359.2019.1681917
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome and phylogenetic analysis of Bombyx mandarina strain Shiquan

Abstract: Bombyx mandarina is generally thought to be the wild ancestor nearest to the domesticated silkworm, Bombyx mori. Here, we report the complete mitochondrial genome (mitogenome) of B. mandarina strain Shiquan. The mitogenome contains 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and one A þ T-rich region. Phylogenetic analysis provides solid evidence that B. mandarina Shiquan belongs to Chinese B. mandarina, rather than Japanese B. mandarina. The new mitogenome provides useful information to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…An examination of the likelihood scores from 10 replicate runs across K values from 1 to 10 for BAPs analysis revealed that available B. mori strains and B. mandarina individuals were composed of four optimal haplotype clusters ( K = 4; hereafter referred to as haplogroups). The assignment results of K = 4 showed that B. mori strains from all countries are composed of a single haplogroup, whereas B. mandarina populations are composed of three haplogroups, which are strictly concordant to their geographic origins, except for one individual of B. mandarina collected in Shiquan, southern China [ 43 ] ( Figure 1 and Figure 3 ). B. mandarina individuals from northern China (including Shiquan) and South Korea shared an identical haplogroup (green), whereas individuals from southern China (excluding Shiquan, light blue) and Japan (red) had an independent haplogroup ( Figure 3 A), suggesting genetic similarity of B. mandarina only between northern China (including Shiquan) and South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An examination of the likelihood scores from 10 replicate runs across K values from 1 to 10 for BAPs analysis revealed that available B. mori strains and B. mandarina individuals were composed of four optimal haplotype clusters ( K = 4; hereafter referred to as haplogroups). The assignment results of K = 4 showed that B. mori strains from all countries are composed of a single haplogroup, whereas B. mandarina populations are composed of three haplogroups, which are strictly concordant to their geographic origins, except for one individual of B. mandarina collected in Shiquan, southern China [ 43 ] ( Figure 1 and Figure 3 ). B. mandarina individuals from northern China (including Shiquan) and South Korea shared an identical haplogroup (green), whereas individuals from southern China (excluding Shiquan, light blue) and Japan (red) had an independent haplogroup ( Figure 3 A), suggesting genetic similarity of B. mandarina only between northern China (including Shiquan) and South Korea.…”
Section: Resultsmentioning
confidence: 99%
“…For the comparative analysis, publicly available mitogenome sequences of the B. mori strains and B. mandarina individuals were downloaded from the GenBank database ( Table S1 ). These consisted of 28 domesticated silkworm strains that originated from eight countries (China, Cambodia, India, Italy, Korea, Japan, Laos, and Russia) and Europe [ 10 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and 17 wild silkworms collected from China and Japan [ 10 , 23 , 43 , 44 , 45 , 46 ] ( Table S1 ). Consequently, 45 public data entries and our own 41 mitogenome sequences, totaling 86 mitogenome sequences of Bombyx , were used for the genomic, phylogeographic, and phylogenetic analyses, along with two Bombyx species downloaded as outgroups in phylogenetic analyses [ 47 , 48 ] ( Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation